SFlt-1 value predicts pregnancy prolongation periods from diagnosis in pregnant women diagnosed with early-onset preeclampsia. (2nd November 2022) - Tanaka, Hiroaki; Nagahashi, Yuko; Toriyabe, Kuniaki; Maki, Shintaro; Takakura, Sho; Enomoto, Naosuke; Tanaka, Kayo; Shinji, Katsuragi; Ikeda, Tomoaki
Abstract: Purpose: The aim of this study is to analyze whether soluble fms-like tyrosine kinase-1 (sFlt-1) can be correlated with the severity of PE. Materials and methods: This study was conducted in a single hospital and is a prospective, observational study. sFlt-1 was measured at the diagnosis of preeclampsia. The period from diagnosis to pregnancy termination (pregnancy prolongation periods) was defined as the barometer for the severity of PE. The correlations between sFlt-1 level with pregnancy prolongation periods were then analyzed. Results: Eighteen pregnant women diagnosed with early-onset preeclampsia were recruited. sFlit-1 value significantly negatively correlated with the pregnancy prolongation period from diagnosis ( p  = .003, R  = 0.647). Conclusion: sFlt-1 was correlated with the pregnancy prolongation periods after onset of PE. sFlt-1 in early-onset PE may reflect the severity of PE in pregnant women.